Remembering erasure: reconstructions of first world war memory in William Kentridge’s the head & the load and David Diop’s at night all blood is black - Esterhuyse, Rene Elizabeth (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMus)--Stellenbosch University, 2023.